FAKTA DAN OPINI PADA TAJUK RENCANA “HARIAN ANALISA” TAHUN 2020 - Khanati Gulo; Merri C. Zalukhu; Anita Zagoto (Universitas Nias Raya, 2021)
This research is motivated by the uniqueness. One of the unique things found in the